Human Resources Strategy in Dealing with Quiet Quitting Among Millennials - Fauziah F Farawowan; Sian Linda Lerebulan; Nurul Fadhilah; Amalia Tasya (PT. Hafasy Dwi Nawasena, 2025)
The phenomenon of quiet quitting reflects employee disengagement due to an imbalance between organizational demands and the fulfillment of individual psychological needs, especially among the millennial generation. Different from conventional resignations, quiet quitting refers to a passive attitude where employees only work to the minimum without emotional involvement or desire to grow. The millennial generation who demand meaning, autonomy, and life balance tend to do quiet quitting when the organization fails to create an inclusive, supportive, and flexible workspace. This study uses a qualitative approach with a literature study method to examine how human resource management (HR) strategies can respond to this phenomenon adaptively. The results of the study show that conventional managerial approaches that are transactional and hierarchical are no longer relevant. In contrast, strategies based on human-centered management, Agile HR, and personalized employee experience have proven to be more effective in building employee engagement and loyalty. Data-based technology is also an important tool in understanding employee needs and aspirations in real time. Therefore, HR strategy transformation is a must to create a relevant, healthy, and sustainable work culture in the modern work era.